Risk factors for metabolic bone disease among preterm infants less than 32 weeks gestation with Bronchopulmonary dysplasia - Wenwen Chen; Zhenhai Zhang; Shuzhen Dai; Liping Xu (BMC, 2021)
Abstract Background Bronchopulmonary dysplasia (BPD) infants present an increased incidence of metabolic bone disease (MBD), but it is unknown which factors contribute to this. The aim of this study was to determine the risk factors for developing MBD in BPD infants. Methods A retrospective review of the medical records of BPD infants admitted to the Neonatal intensive care unit at Zhangzhou Hospital between Jun 2016 and May 2020 was performed. BPD infants with MBD were identified, two contemporaneous without MBD matched by gestational age and gender were randomly selected as controls for each case of MBD. The association between putative risk factors and MBD was estimated with ORs and 95% CIs. A P-value threshold ≤0.2 was used in univariate analysis for inclusion into a multivariate (adjusted) model with a P-value of < 0.05 as statistically significant. Results A total of 156 BPD infants were enrolled with 52 cases of MBD and 104 controls. Fetal growth restriction (OR 6.00, 95% CI, 1.81-19.84), extremely low birth weight (OR 3.10, 95% CI, 1.07-8.94), feeding volume < 80 mL/kg/d at the end of the 4th week after birth (OR 14.98, 95% CI, 4.04-55.58), cholestasis (OR 4.44, 95% CI, 1.59-12.40), late onset sepsis (OR 3.95, 95% CI, 1.12-13.98) and prolonged (> 2 weeks) diuretics application (OR 5.45, 95% CI, 1.25-23.84) were found to be statistically significant risk factors for MBD in BPD infants. Conclusion In BPD infants of homogeneous gestational age, fetal growth restriction, extremely low birth weight, feeding volume < 80 mL/kg/d at the end of the 4th week after birth, cholestasis and late onset sepsis are significant risk factors for MBD. These findings provide potential predictive factors for MBD in BPD infants and warrant prospective validation.